2009
DOI: 10.2337/db09-0387
|View full text |Cite
|
Sign up to set email alerts
|

Virus-Induced Autoimmune Diabetes in the LEW.1WR1 Rat Requires Iddm14 and a Genetic Locus Proximal to the Major Histocompatibility Complex

Abstract: OBJECTIVETo identify genes that confer susceptibility to autoimmune diabetes following viral infection in the LEW.1WR1 rat.RESEARCH DESIGN AND METHODSAbout 2% of LEW.1WR1 rats develop spontaneous autoimmune diabetes. Immunological perturbants including viral infection increase both the frequency and tempo of diabetes onset. To identify diabetes susceptibility genes (LEW.1WR1 × WF), F2 rats were infected with Kilham rat virus following brief pretreatment with polyinosinic:polycytidylic acid. This treatment indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 48 publications
1
28
0
Order By: Relevance
“…For these studies we used LEW1.WR1 rats, which develop T1D in response to rat cytomegalovirus (RCMV) infection with the same frequency and time course as BBDR rats in response to KRV (23). In our studies we found that 22% (3 of 11) of LEW1.WR1 rats treated with a single dose of RCMV developed diabetes within 16 days (Figure 5a).…”
Section: Resultsmentioning
confidence: 99%
“…For these studies we used LEW1.WR1 rats, which develop T1D in response to rat cytomegalovirus (RCMV) infection with the same frequency and time course as BBDR rats in response to KRV (23). In our studies we found that 22% (3 of 11) of LEW1.WR1 rats treated with a single dose of RCMV developed diabetes within 16 days (Figure 5a).…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, the ability of KRV to induce T1D in LEW.1WR1 and BBDR rats declines with age (45, 49), and suggests that developmental changes in susceptible hosts are determinants of viral diabetogenicity. Relevant to the low rate of T1D progression among human carriers of high risk HLA haplotypes, such viral induction protocols do not induce T1D in MHC-matched Wistar-Furth rats, suggesting that factors beyond the MHC are necessary for viral induction of T1D (51, 52). The ability to induce diabetes within the context of high genetic risk in an age-dependent manner is a significant attribute of the BBDR and LEW1.WR1 rat models that may parallel human diabetogenesis.…”
Section: Evidence Of Viral Triggering Of T1d In Genetically Susceptibmentioning
confidence: 99%
“…Previous studies showed that administration of poly (I:C) either prevents or accelerates diabetes development in NOD mice or BB rats depending on the doses or kinetics of poly (I:C) action [47-49]. However, administration of poly(I:C) can accelerate virus-induced diabetes in BBDR rats that are normally resistant to T1D development [50]. This suggests that dsRNA sensors, such as TLR3, as well as two RLRs, retinoic acid-inducible gene I (RIG-I) and melanoma differentiation-associated gene-5 (MDA5), can promote diabetes in an IFN-dependent manner, as activation of all of these innate receptors induces strong type 1 interferon responses.…”
Section: Tlrs and T1dmentioning
confidence: 99%
“…Although the precise role of viruses in the pathogenesis of T1D remains controversial, previous studies from both mouse models and human patients have revealed that viral infection might be associated with T1D development [50-55]. The induction of prion-inflammatory cytokines by viral infection could affect islet autoimmunity and β-cell decay.…”
Section: Tlrs and T1dmentioning
confidence: 99%